MLL2 conveys transcription-independent H3K4 trimethylation in oocytes - Hanna, Courtney W; Taudt, Aaron; Huang, Jiahao; Gahurova, Lenka; Kranz, Andrea; Andrews, Simon; Dean, Wendy; Stewart, A Francis; Colomé-Tatché, Maria; Kelsey, Gavin (Nature structural & molecular biology, 2018)
Histone 3 K4 trimethylation (depositing H3K4me3 marks) is typically associated with active promoters yet paradoxically occurs at untranscribed domains. Research to delineate the mechanisms of targeting H3K4 methyltransferases is ongoing. The oocyte provides an attractive system to investigate these mechanisms, because extensive H3K4me3 acquisition occurs in nondividing cells. We developed low-input chromatin immunoprecipitation to interrogate H3K4me3, H3K27ac and H3K27me3 marks throughout oogenesis. In nongrowing oocytes, H3K4me3 was restricted to active promoters, but as oogenesis progressed, H3K4me3 accumulated in a transcription-independent manner and was targeted to intergenic regions, putative enhancers and silent H3K27me3-marked promoters. Ablation of the H3K4 methyltransferase gene Mll2 resulted in loss of transcription-independent H3K4 trimethylation but had limited effects on transcription-coupled H3K4 trimethylation or gene expression. Deletion of Dnmt3a and Dnmt3b showed that DNA methylation protects regions from acquiring H3K4me3. Our findings reveal two independent mechanisms of targeting H3K4me3 to genomic elements, with MLL2 recruited to unmethylated CpG-rich regions independently of transcription.
Keywords: Animals; Markov Chains; Myeloid-Lymphoid Leukemia Protein; sekvenční analýza RNA; Chromatin Immunoprecipitation; histonlysin-N-methyltransferasa; Female; Oogenesis; Mouse Embryonic Stem Cells; myší embryonální kmenové buňky; chromatinová imunoprecipitace; multivariační analýza; CpG ostrůvky; oogeneze; ženské pohlaví; Mice, Knockout; myši knockoutované; Multivariate Analysis; Oocytes; Transcription, Genetic; Mice; oocyty; metylace DNA; myši; CpG Islands; genetická transkripce; Histone-Lysine N-Methyltransferase; Markovovy řetězce; DNA Methylation; histony; Histones; promotorové oblasti (genetika); zvířata; Promoter Regions, Genetic; Mice, Inbred C57BL; Sequence Analysis, RNA; protoonkogenní protein MLL; myši inbrední C57BL